Negative thermal expansibility change for dissociation of lysozyme variant amyloid protofibril - Ishiguro, Ryo; Matsuo, Hiroshi; Kameyama, Keiichi; Tachibana, Hideki; Fujisawa, Tetsuro (Electrophoresis, 2015)
A disulfide‐deficient variant of hen lysozyme, 0SS, is known to form an amyloid protofibril spontaneously, and to dissociate into monomers at high hydrostatic pressure. We carried out native PAGE at various temperatures (20–35°C) and pressures (0.1–200 MPa), to characterize the dissociation equilibrium of disulfide‐deficient variant of hen lysozyme amyloid protofibril. Based on the density profiles, the partial molar volume and thermal expansibility changes for dissociation, ΔvD and ΔeD, were obtained to be −74 cm3/mol at 25°C and −2.3 cm3 mol−1 K−1, respectively. The dissociation of amyloid fibril destroys the cross β‐structure, and such conformational destruction in native protein fold rarely accompanies negative thermal expansibility change. We discussed the negative thermal expansibility change in terms of hydration and structural packing of the amyloid protofibril.